PROGRAM PEMENUHAN HAK-HAK ANAK DI KECAMATAN MEUREUBO KABUPATEN ACEH BARAT (GEUNASEH: Jurnal Kajian Gender, Anak dan Sosial Inklusi, 2025)
This study aims to analyze the fulfillment of basic children's rights in Meureubo District, West Aceh Regency. This study uses a qualitative approach with informant selection techniques through purposive sampling, data collection techniques are carried out through observation, interviews, and documentation. The results of the study are: in an effort to fulfill children's rights, the Meureubo District Government has created several child-friendly programs, namely: a. Forming a village towards being child-friendly; b. Health centers with child-friendly services; c. Child-friendly Islamic boarding schools; and d. Children's forums. The communities in the research area are trying to fulfill children's basic rights in each cluster of children's rights, but not optimally. This could be due to several factors such as limited human resources, limited budget, and the commitment of leaders and policy implementers is not yet strong